ATP-Induced Ca(2+) Release in Cochlear Outer Hair Cells: Localization of an Inositol Triphosphate-Gated Ca(2+) Store to the Base of the Sensory Hair Bundle - Mammano, Fabio (J Neurosci, 1999)
We used a high-performance fluorescence imaging system to visualize rapid changes in intracellular free Ca(2+)concentration ([Ca(2+)](i)) evoked by focal applications of extracellular ATP to the hair bundle of outer hair cells (OHCs): the sensory–motor receptors of the cochlea. Simultaneous recordings of the whole-cell current and Calcium Green-1 fluorescence showed a two-component increase in [Ca(2+)](i). After an initial entry of Ca(2+) through the apical membrane, a second and larger, inositol triphosphate (InsP(3))-gated, [Ca(2+)](i) surge occurred at the base of the hair bundle. Electron microscopy of this intracellular Ca(2+) release site showed that it coincides with the localization of a unique system of endoplasmic reticulum (ER) membranes and mitochondria known as Hensen’s body. Using confocal immunofluorescence microscopy, we showed that InsP(3)receptors share this location. Consistent with a Ca(2+)-mobilizing second messenger system linked to ATP-P2 receptors, we also determined that an isoform of G-proteins is present in the stereocilia. Voltage-driven cell shape changes and nonlinear capacitance were monitored before and after ATP application, showing that the ATP-evoked [Ca(2+)](i)rise did not interfere with the OHC electromotility mechanism. This second messenger signaling mechanism bypasses the Ca(2+)-clearance power of the stereocilia and transiently elevates [Ca(2+)](i) at the base of the hair bundle, where it can potentially modulate the action of unconventional myosin isozymes involved in maintaining the hair bundle integrity and potentially influence mechanotransduction.